In Vivo Induction of Virulence and Antibiotic Resistance Transfer in Enterococcus faecalis Mediated by the Sex Pheromone-Sensing System of pCF10 - Hirt, Helmut (American Society for Microbiology, 2002)
Enterococcus faecalis has become one of the most notable nosocomial pathogens in the last decade. Aggregation substance (AS) on the sex pheromone plasmids of E. faecalis has been implicated as a virulence factor in several model systems. We investigated the AS-encoding plasmid pCF10 for its ability to increase virulence in a rabbit endocarditis model. Cells containing pCF10 increased the virulence in the model significantly, as assessed by an increase in aortic valve vegetation size. The results confirmed in vivo induction of the normally tightly controlled AS. In addition to the expression of AS when E. faecalis cells were in contact with plasma, plasmid transfer of the tetracycline resistance-carrying plasmid was also activated in vitro and in vivo. In vivo, plasmid transfer reached remarkable frequencies of 8 × 10(−2) to 9 × 10(−2). These values are comparable to the highest frequencies ever observed in vitro. Cells harboring pCF10 had a significant survival advantage over plasmid-free cells indicated by pCF10 present in two-thirds of the recipient population. Plasma induction was dependent on the presence of the plasmid-encoded PrgZ protein, indicating the requirement of the pheromone-sensing system in the induction process. The data suggested that the mechanism of in vivo induction may involve interference of plasma with the normal function of the pheromone peptide and its inhibitor.